Corporate ethics, governance, and social responsibility : precepts and practices - Fernando, A. C., 1940- (Pearson Power, Dorling Kindersley, 2009)
Is profit-making the only goal of a business? Should an unbridled market mechanism drive corporate enterprise? To what extent should corporations compensate for the manifest and hidden costs that are incurred by the society at large? Corporate Ethics,